Evolution : the first four billion years - Ruse, Michael; Travis, Joseph, 1953- (Belknap Press of Harvard University Press, 2009)
An introduction to evolutionary biology, with sixteen essays about the history and philosophy of the field, related empirical and theoretical questions about topics such as speciation, adaptation, and development, and articles on important figures, social and political issues, and related religious topics.